Rain and its impact on Iraq’s watery future - Al-Rubai, Nasr Shamil Salman Hassan; Al-Hathal, Youssef Mohammed Ali Hatem (Al-Adab Journal, 2021)
The research aims to study the trend of rains in Iraq during the years 1941 to 2017 and in the form of seasonal data starting from September to May, including (76) seasons. Ten study stations were selected spatially distributed throughout Iraq. As for the statistical work in this research, it was based on the extraction of Values ​​of the trend equation for the total rainfall during the rainy season, and then determining the amount of change in the direction during the time series to determine the water future for Iraq, although Iraq relies on feeding the waters of the Tigris and Euphrates rivers on the source countries, but rainfall remains the basis for feeding the sources and rivers in addition to Exploitation of the quantities of falling rain and the resulting torrents in the water harvest, as these water quantities are an important support for river water.